Ausencia parental y entorno educativo en estudiantes de décimo grado en la Unidad Educativa Pío Jaramillo Alvarado, ciudad Loja, período 2024-2025 - Guanuche Saritama, Scarleth Anahí (2025)
The present Curricular Integration work was aimed to analyze the impact of parental absence on the academic environment of tenth grade students of Pío Jaramillo Alvarado Educational Unit during the period 2024-2025; It was a qualitative study, descriptive scope, non-experimental and cross-sectional design. Data collection involved structured interviews and observation sheets were applied to the sample of 1 DECE (Student Counseling Department) analyst and 1 tutor teacher from the institution. The results show that parental absence has a negative impact on the emotional stability, academic motivation and interpersonal relationships of the students. The study identified several causes of this absence such as: long working hours that prevent the physical parents presence, migration in search of better job opportunities, the death of a parent, emotional issues that affect the ability of parents to provide accompaniment and support, family conflicts that result in distancing or separation. These situations create an emotional void that impacts students’ academic performance and emotional well-being, hindering their ability to cope with daily challenges. Consequently, the research highlights the need to develop a guide for parents with activities to provide them necessary tools to support their children's academic and emotional well-being. This work concludes that parental absence negatively impacts the academic and emotional development of tenth grade students, emphasizing the critical role of parental involvement in the educational process